Triglyceride-glucose index, renal function, sleep duration, and myocardial infarction: a UK biobank cohort study - Liu, Zeyan; Wang, Jinbo; Pan, Xiaodong; Zhang, Pan; Yang, Min; Zhang, Ye (Frontiers in Nutrition, 2025)
BackgroundMyocardial infarction (MI) remains a leading cause of cardiovascular morbidity and mortality globally. Insulin resistance, renal function, and sleep duration are key risk factors, yet their combined impact on MI risk is underexplored.MethodsIn this UK Biobank cohort study, 415,757 participants were included. Cox proportional hazards models estimated hazard ratios (HRs) for MI risk across quartiles of triglyceride-glucose (TyG) indices (TyG, TyG-BMI, TyG-WC, TyG-WHTR), stratified by eGFR and sleep duration categories. Mediation analyses evaluated interrelationships among TyG indices, eGFR, sleep duration, and MI.ResultsOver follow-up, 13,484 participants developed MI. Higher TyG indices were associated with increased MI risk; TyG-WHTR showed the strongest effect (Q4 vs. Q1, HR: 1.90, 95% CI: 1.76–2.06). Reduced eGFR (<60) was linked to higher MI risk (HR: 1.71, 95% CI: 1.51–1.93), as were short (<7 h; HR: 1.20, 95% CI: 1.11–1.29) and long (>9 h; HR: 1.43, 95% CI: 1.22–1.68) sleep durations. TyG-MI associations were significant in participants with preserved renal function (eGFR ≥60) and short/normal sleep. Mediation analyses revealed that eGFR and sleep duration partially mediated the associations between TyG indices and MI risk, and vice versa, indicating complex interrelations.ConclusionTyG-related indices are valuable predictors of MI risk, particularly in individuals with preserved renal function and typical sleep duration. The interplay among insulin resistance, renal function, and sleep patterns underscores the importance of integrated metabolic and lifestyle factors in cardiovascular risk stratification.